A Qualitative Scoping Review of Transgender and Gender Non-conforming People's Physical Healthcare Experiences and Needs - Teti, Michelle; Kerr, Steffany; Bauerband, L. A.; Koegler, Erica; Graves, Rebecca (Frontiers in Public Health, 2021)
Trans and gender non-conforming (TGNC) people experience poor health care and health outcomes. We conducted a qualitative scoping review of studies addressing TGNC people’s experiences receiving physical health care to inform research and practice solutions. A systematic search resulted in thirty-five qualitative studies for analysis. Studies included 1607 TGNC participants, ages 16 to 64 years. Analytic methods included mostly interviews and focus groups; the most common analysis strategy was theme analysis. Key themes in findings were patient challenges, needs, and strengths. Challenges dominated findings and could be summarized by lack of provider knowledge and sensitivity and financial and insurance barriers, which hurt TGNC people’s health. Future qualitative research should explore the experiences of diverse and specific groups of TGNC people (youth, non-binary, racial/ethnic minority), include community-based methods, and theory development. Practice-wise, training for providers and skills and support for TGNC people to advocate to improve their health, are required.